Studi Kritis Hadis Prediktif tentang Dajjal dengan Pendekatan Hermeneutika Gracia - Alma’arif Alma’arif (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Hadiths that were revealed in the 7th century in the Arabian nation have historical and normative content. Hadith in the historical framework means that it cannot be separated from the horizon, culture and patrons that surround it. Meanwhile, the hadith in the normative framework means the teachings and values contained in the hadith. Knowing which one is historical and which one is relative must be done with various approaches so as not to be trapped in a rigid and static meaning that causes the hadith to be overtaken by the times. This article aims to examine the understanding of the predictive hadith about Dajjal using Gracia's hermeneutic approach. Gracia in relation to dissecting the text divides it into three aspects; namely historical function, meaning function and implicative function. Through Gracia's approach, it can be concluded that the traditions related to Dajjal are historical and in accordance with the context in which they were delivered to the audience at that time. Hadiths about Dajjal that are historical in nature cannot be understood contextually as the original text, because holding on to the original text will contradict the context and the development of science. For example, the issue of swords, close-range warfare and so on. The Hadith of Dajjal as an implicative meaning can be interpreted as anyone who deceives and causes damage on earth, making it more universal and accepted by all groups.